International journal of grid and high performance computing - IGI eBooks; IGI Global (Hershey, Pa. : IGI Global (701 E. Chocolate Avenue, Hershey, Pa., 17033, USA), 2009)
The International Journal of Grid and High Performance Computing (IJGHPC) examines current, state-of-the art research on all aspects of grid and cloud evolution, middleware, standards, API, economy, education, services, algorithms, collaboration, impact, instrumentation, security, portals, trends, challenges, models, work flow management, wireless systems, and high performance computing. This journal will be instrumental in the improvement and development of theory and practice in grid and cloud computing.
Also available in print.
Mode of access: World Wide Web.
Description based on: Vol. 1, no. 1 (Jan./Mar. 2009); title from title screen (IGI Global, viewed Oct. 1, 2010).
Latest issue consulted: Vol. 2, no. 3 (2010).
Keywords: Computational grids (Computer systems) -- Periodicals; High performance computing -- Periodicals; Collaboration techniques and scaling issues; Algorithms and techniques for HPC; Bio-inspired grid resource management; Cloud architectures; Cloud business process integration; Cloud client and applications; Cloud foundation concepts; Cloud platforms and infrastructures; Cloud reliability and security; Cloud services; Cloud standards; Cloud types; Global terrorism; Emerging standards; Future of grid, trends, and challenges; Grid and software engineering aspects; Grid architecture, resources, and data management; Grid economy, market dynamics, and simulations; Grid education and applications; Grid evolution, characterization, and concepts; Grid impact; Grid portals and security; Grid programming, models, tools, and API; Grid uses and emerging technology; New initiatives, SOA, autonomic computing, and semantic grid; Simple API for grid applications (SAGA); Software and hardware support for HPC; Test, evaluation, and certificate presentation; Wireless and optical grid, characteristics, and applications; Work flow management; Electronic books